Utilization of activated carbon derived from waste plastic for decontamination of polycyclic aromatic hydrocarbons laden wastewater - Muhmmad Ilyas (IWA Publishing, 2021)
Serious environmental deterioration caused by synthetic waste plastics, and the pollution of freshwater resources are the most alarming and marked challenges of the 21st century. Therefore, immense scientific efforts are being made towards the management of waste plastics and treatment of polluted water. The current study reports on the utilization of waste polyethylene terephthalate (wPET) and waste polystyrene (wPS) for fabrication of activated carbon (AC) and its application for the removal of hazardous polycyclic aromatic hydrocarbons (PAHs) pollutants from water. AC was prepared from wPET and wPS by carbonization under a N2 atmosphere followed by chemical activation with 1 M KOH and 1 M HCl. The AC was characterized by scanning electron microscopy, surface area analysis, and Fourier transform infrared spectroscopy. Adsorption of PAHs from aqueous solutions through AC was examined by batch adsorption tests. The optimum parameters for maximum adsorption of PAHs were found to be: initial PAHs concentration 40 ppm, 2 h contact time, pH 3, 5, and 7, 50 °C temperature and adsorbent dose of 0.8 g. Kinetic and isotherm models were applied to evaluate the adsorbent capacity for PAHs adsorption. The kinetic study shows that the adsorption of these PAHs onto AC follows pseudo-second-order kinetics. The experimental results demonstrated that the Langmuir isotherm model best fitted the data. The thermodynamic factors calculated such as entropy change (ΔS°), enthalpy change (ΔS°) and free energy change (ΔG°) show that the adsorption process is non-spontaneous and endothermic in nature. Results were also compared with the efficiencies of some commercial adsorbents used in practice. This examination revealed that the novel plastic-derived AC possesses a great potential for elimination and recovery of PAH elimination from industrial wastewater. HIGHLIGHTS AC was prepared from wPET and wPS by carbonization followed by chemical activation.; Adsorption of PAHs from aqueous solutions through AC was examined by batch adsorption tests.; PAH adsorption from the aqueous solutions follows pseudo-second-order kinetics.; The experimental data are best fitted to the Langmuir isotherm model.; AC possesses a large potential for elimination and recovery of PAHs from wastewater.;